Production of organic fertilizer using pleurotus sp. as a process accelerator - A. Medina-Buelvas; A. Garcia-Guan; B. Barraza-Amador; E. Espinosa-Fuente; M. Del Castillo-Cabrales; K. Mendez-Gutiérrez; N. Rosales-Hernández (Global Journal of Environmental Science and Management)
BACKGROUND AND OBJECTIVES: One of the best retributions that man can make to the environment and that promotes development is the incorporation of waste into truly productive processes. In this sense, the main objective of this study was to take advantage of the vegetal residues from tree pruning obtained from the maintenance of the overhead wiring of the electrical networks in the city of Barranquilla, in Colombia, to produce an organic fertilizer, which are some of the most demanded products in the world. The production of organic fertilizer was carried out by composting using the Pleurotus sp. fungus as an accelerator of the process.METHODS: For compost production, three treatments were used based on a mixture of manure, pruning, banana bagasse and Pleurotus sp. as an accelerator process. Each treatment was layered and then arranged in beds of compost piles. The temperature and humidity were monitored throughout the process. Physicochemical parameters were measured at the end of the process in concordance with the Colombian Technical Standard 5761. To evaluate the biological efficiency of the compost, two doses were tested with each 100 gram and 200 gram of fertilizer for each 500 gram of soil using corn seeds, which were sown in bags over a period of three months. At the end of the test, biological growth parameters such as foliar development, amount of biomass and fruiting were measured.FINDING: Most of the physicochemical and biological parameters were within the NTC 5167 standard. The treatment with the highest percentage of degradation by composting was treatment number 2 (with Pleurotus sp.), which showed that with 60 percent of fresh prunings in the formulation, Pleurotus accelerates the process by 24 percent compared to the other treatments.CONCLUSION: In summary, the tested method is a good route to produce fertilizers from pruning wastes. Regarding the effect of the fertilizer on the development of corn seedlings, a positive effect was observed compared to the control. Otherwise, in the composting process, the fungus significantly accelerates the process and at the same time shows an overgrowth.